'As Good as New' – Sale of Repaired or Refurbished Goods: Commendable Practice or Trade Mark Infringement?. Issue 3 (23rd January 2021) - Kur, Annette
Abstract: Prolonging the life cycle of products in order to reduce waste and preserve resources is a call of our time. Entrepreneurial activity on the market for used and repaired goods should therefore be encouraged. However, problems may arise where trade-marked products are offered for sale after repair or refurbishment by third parties. While commercialisation of goods once put on the market by the trade mark holder or with their consent is free in principle, this does not apply when the condition of the product was changed after the first sale. This may cause a dilemma for persons who want to be active on the secondary market for repaired or refurbished goods: if the trade mark remains on the product, this may result in infringement; on the other hand, under the jurisprudence of the CJEU removal of the trade mark may equally be prohibited. This article explores the issue with a view to CJEU as well as German case law on this and adjacent scenarios. It concludes that instead of a strictly binary choice – either the trade mark remains on the product or is removed – a middle solution should apply that allows using the trade mark in relation to repaired or refurbished goods in addition to providing further information.